Malay Arabic Script: Shifting Theology towards the Construction of Identity in Malays Civilization - Dewi, Eva; Munthe, Bermawy; Amrulloh, Muhammad Afif; Darmawi, Ahmad; Martina, Arbi Feny; Martina, Feny; Wekke, Ismail Suardi (International Journal of Psychosocial Rehabilitation, 2020)
Malay Arabicscript is an Arab script that is collaborated with Malays. The introduction of Arabic script to the Malay society has a long process. The emergence of theMalay Arabic Script is explained when there was a pebble as a proof that is inscribed in Kuala Berang Trengganu on Friday, 4 Rajab 702 H and February 221303 AD. But, the Malay Arabic Scriptwas lost and abolished during the New Order era, reappeared and revived in the Reform era with the regional autonomy system of government. This phenomenon raises an academic question, why did Malay Arabic Scriptrise again? Does the effort of the revivalization of Arabic script of Malay is reflection of the theological Malays in their aspect of life, or does the use ofMalay Arabic script as a symbol of identity of Malay society?To answer this problem, the author used a sociolinguistic and historical approach. Whereas, the theory that used is the theory of social constructivism by Peter L. Berger and Thomas Luckmann’s. The reality showed that the Malay Arabic Scriptexperienced a shift in meaning (values) for the Malays. TheMalay Arabic Scripttoday is not only used as a theological interest or as a direction of a practice that related to religiosity. However, nowadays, the existence of theMalay Arabic Scriptin Riau is used as a tool of legitimacy for the existence and interests of individuals, groups and institutions. Identity construction is carried out in the form of objectivation, internalization and externalization. Indeed, the action is to strengthen the identity of the Riau region in accordance with the Vision of Riau 2020 which makes Riau a Malay Cultural Center in Southeast Asia.